The role of universities in regional economic development based on tourism in Lampung - Faurani Santi Singagerda; Anuar Sanusi (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to analyze the role of universities in economic development in the areas of tourism-based communities in Lampung. This study uses secondary data related to tourism, higher education, and macroeconomics of Lampung Province during the period of 2000-2016. The analysis is done by using panel regression method. The results show that Higher Education plays an enormous role in the economic development of the economy in the blood-based areas of tourism and which has tourism potential in Lampung. Most of the villagers who are in tertiary education but work in urban areas as a weakness of their contribution and domino effect on low investment, welfare, and lack of employment. This is why they are wandering to the big city. There is also a social gap which has significant economic disparities. They have access to education, health, and supporting infrastructure. In terms of the number of existing universities, it was found that they have not been able to optimally improve economic development in these areas.